The COVID-19 Pandemic Related Lived Experiences of Individuals With a Spinal Cord Injury/Disease - Simpson, Ethan; Miller, William C.; Schmidt, Julia; Borisoff, Jaimie; Mortenson, W. Ben (Frontiers in Rehabilitation Sciences, 2022)
Introduction: COVID-19 related restrictions and recommendations have impacted everyone. Those living with a disability, such as individuals with a spinal cord injury (SCI), may have had pandemic related changes made yet more challenging by societal failures to accommodate their mobility, physical abilities, and health care needs. To better understand participants experiences we drew upon Heidegger’s phenomenology and the mobilities paradigm. The objective of this study was to explore COVID-19 pandemic related lived-experiences of individuals with an SCI. Materials and methods: This study used an interpretive phenomenological methodology. Semi-structured interviews were the primary means of data collection. These were conducting in May and June of 2020, roughly 2-3 months into the pandemic. Transcript data were analysed using a phenomenological methodology. Results: We interviewed 22 participants with SCI, the mean age was 54 years, and nine were females. We identified three themes: 1) Experiencing changes to mobility and daily life described how new rules had impacted everyday life and usual routines, particularly in regard to mobility. 2) Struggling with new challenges explored some of the negative experiences of the pandemic. 3) Being resilient in the face of a new normal conveyed the resilience participants exhibited despite challenges. Conclusion: Although our findings indicate some positive changes and highlight the strengths that many individuals with SCI have, they also accentuate issues with ableism within the medical system. Certain changes were made primarily because people without disabilities needed them, and several COVID-19 changes were made without consulting individuals with disabilities. With physical movement restricted, our findings emphasise the importance of the movement of information and a need for increased dialogue with people in the SCI community about their ongoing pandemic related needs.